2020
DOI: 10.1021/acsami.0c01182
|View full text |Cite
|
Sign up to set email alerts
|

Flexible MXene-Decorated Fabric with Interwoven Conductive Networks for Integrated Joule Heating, Electromagnetic Interference Shielding, and Strain Sensing Performances

Abstract: Although flexible and multifunctional textile-based electronics are promising for wearable devices, it is still a challenge to seamlessly integrate excellent conductivity into textiles without sacrificing their intrinsic flexibility and breathability. Herein, the vertically interconnected conductive networks are constructed based on a meshy template of weave cotton fabrics with interwoven warp and weft yarns. The two-dimensional early transition metal carbides/nitrides (MXenes), with unique metallic conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
194
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(195 citation statements)
references
References 48 publications
1
194
0
Order By: Relevance
“…Due to the increasing demand for exceptional conductive and electrochemical properties for specific application in wearable textiles, conductive polymers and carbon-based materials have been combined with emerging MXenes [131,132] to fabricate multifunctional e-textiles by spraying. Otherwise, MXenes themselves have already shown their great application in integrated Joule heating, electromagnetic interference shielding and strain sensing when sprayed on fabrics by forming conductive networks (Figure 7c) [127]. Moreover, Mxenes have been incorporated into cellulose-based yarns for textile-based electronic devices [128].…”
Section: Spray Coatingmentioning
confidence: 99%
“…Due to the increasing demand for exceptional conductive and electrochemical properties for specific application in wearable textiles, conductive polymers and carbon-based materials have been combined with emerging MXenes [131,132] to fabricate multifunctional e-textiles by spraying. Otherwise, MXenes themselves have already shown their great application in integrated Joule heating, electromagnetic interference shielding and strain sensing when sprayed on fabrics by forming conductive networks (Figure 7c) [127]. Moreover, Mxenes have been incorporated into cellulose-based yarns for textile-based electronic devices [128].…”
Section: Spray Coatingmentioning
confidence: 99%
“…Various researches on the compound of conductive materials and flexible substrates have emerged. For example, Cai and co-workers designed a versatile and scalable strain sensor based on transition metal carbides or nitrides MXene (Ti 3 C 2 T X ), carbon and excellent hydrophilicity, MXene (Ti 3 C 2 T X ) have manifested superior performance in fields of energy storage, [21] sensors, [7,22] batteries, [23] electromagnetic shielding, [24] thermal management, [24,25] and other eco-friendly applications. [26] In addition, the presence of sufficient functional groups (O, OH, F, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[27] Zhang et al constructed flexible and MXene-decorated textile electronics based on vertically interconnected conductive network, demonstrating an integrated Joule heating, EMI shielding, and strain sensing performances. [25] Li et al reported a multifunctional composite film with nacre-like nanostructure based on MXene and montmorillonite, which were highly promising for electromagnetic shielding, de-icing, thermal management, and fire protection. [28] Furthermore, it has been reported that Ag NPs can effectively enhance the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve a conductive polyamide, several methods have been adopted in recent years, which can be classified into two types according to the categories of antistatic agents. First, conductive nanoparticles [ 8 , 9 ], including carbon nanotubes [ 10 , 11 , 12 , 13 ], graphene [ 14 , 15 , 16 , 17 , 18 ] and carbon black [ 19 , 20 , 21 , 22 ], have been popular for use in fabricating polyamide-based nanocomposites. Here, enhancing the interfacial adhesion between nanopowders and the corresponding matrix has attracted a great deal of attention as it determines the ultimate properties of the composites.…”
Section: Introductionmentioning
confidence: 99%